2017
DOI: 10.1007/s12549-016-0262-z
|View full text |Cite
|
Sign up to set email alerts
|

Occurrences of Sinolagomys (Lagomorpha) from the Valley of Lakes (Mongolia)

Abstract: The genus Sinolagomys is an early representative of the family Ochotonidae, appearing first in the late early Oligocene of Central Asia. It is known in China from Shargaltein Tal, Taben Buluk, Ulan Tatal, and northern Junggaria, and a few specimens from Tatal Gol, Mongolia have been published. For most occurrences, the genus is not represented by many specimens. Extensive studies in the Valley of Lakes, Central Mongolia, have produced a large number of sinolagomyin fossils spanning at least 10 million years an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…With the beginning of the Oligocene, the Desmatolagus lineage became diverse, abundant, and widespread throughout Central Asia (Sych, 1975;Huang, 1987;Wang, 2007), surviving until the Miocene, and possibly entering Europe (Early Oligocene, Vianey-Liaud and Lebrun, 2013) and North America (Late Oligocene; Dawson, 2008). Along with Desmatolagus, in the late Early/Middle Oligocene, the first plausible representatives of crown lagomorphs appear in Asia: Sinolagomys (an early ochotonid from China and Mongolia; see Erbajeva et al, 2017) and Ordolagus (probably an early leporid from China; Bohlin, 1942).…”
Section: The Fossil Recordmentioning
confidence: 99%
“…With the beginning of the Oligocene, the Desmatolagus lineage became diverse, abundant, and widespread throughout Central Asia (Sych, 1975;Huang, 1987;Wang, 2007), surviving until the Miocene, and possibly entering Europe (Early Oligocene, Vianey-Liaud and Lebrun, 2013) and North America (Late Oligocene; Dawson, 2008). Along with Desmatolagus, in the late Early/Middle Oligocene, the first plausible representatives of crown lagomorphs appear in Asia: Sinolagomys (an early ochotonid from China and Mongolia; see Erbajeva et al, 2017) and Ordolagus (probably an early leporid from China; Bohlin, 1942).…”
Section: The Fossil Recordmentioning
confidence: 99%
“…M. Dawson was certainly correct when she suggested that the genus Sinolagomys with its derived characters in tooth morphology may lie at the base of the Bellatona lineage. Among the known species of the genus Sinolagomys, S. badamae Erbajeva (Erbajeva et al, 2017) shows greatest similarity with Bellatona. It is characterized by an elongated trigonid on the p3, which has rounded edges similar to what is observed in Bellatona kazakhstanica.…”
Section: Discussionmentioning
confidence: 99%